2015
DOI: 10.1002/imhj.21498
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Attachment and Emotional Availability Tele-Intervention for Adoptive Families

Abstract: This study evaluated the new online Emotional Attachment and Emotional Availability (EA2) Intervention for use with adoptive families in enhancing parent-child EA, parental perceptions of EA, child attachment behaviors, parent-child emotional attachment, and reducing parent-reported child behavioral problems and parenting-related stress. Participants in this study were adoptive parents and their adopted children ages 1.5 to 5 years old (N = 15 dyads). Participants were placed in an immediate intervention group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
68
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(70 citation statements)
references
References 53 publications
0
68
0
2
Order By: Relevance
“…Eight of the studies examined outcomes related to interpersonal or family functioning (Baker et al, 2015;Baskin et al, 2011;Benjamin, 2010;Carnes-Holt & Bratton, 2014;Chan, 1987;Juffer et al, 2005;Loew et al, 2012;Wassall, 2011). Five of these examined aspects of the interpersonal relationship between a caregiver and the child (Baker et al, 2015;Carnes-Holt & Bratton, 2014;Chan, 1987;Juffer et al, 2005;Wassall, 2011) while three of these studies examined aspects related to romantic relationships (Baskin et al, 2011;Benjamin, 2010;Loew et al, 2012).…”
Section: Summary Of Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Eight of the studies examined outcomes related to interpersonal or family functioning (Baker et al, 2015;Baskin et al, 2011;Benjamin, 2010;Carnes-Holt & Bratton, 2014;Chan, 1987;Juffer et al, 2005;Loew et al, 2012;Wassall, 2011). Five of these examined aspects of the interpersonal relationship between a caregiver and the child (Baker et al, 2015;Carnes-Holt & Bratton, 2014;Chan, 1987;Juffer et al, 2005;Wassall, 2011) while three of these studies examined aspects related to romantic relationships (Baskin et al, 2011;Benjamin, 2010;Loew et al, 2012).…”
Section: Summary Of Resultsmentioning
confidence: 99%
“…Five of these examined aspects of the interpersonal relationship between a caregiver and the child (Baker et al, 2015;Carnes-Holt & Bratton, 2014;Chan, 1987;Juffer et al, 2005;Wassall, 2011) while three of these studies examined aspects related to romantic relationships (Baskin et al, 2011;Benjamin, 2010;Loew et al, 2012). Among studies on aspects of the caregiver's relationship to the child, three out of five studies found positive effects on emotional availability (Baker et al, 2015), empathy (Carnes-Holt & Bratton, 2014), and maternal sensitivity (Juffer et al, 2005), respectively. Wassall (2011) did not formally test for group differences and, thus, it cannot be determined whether the Fostering Attachments intervention had any significant impact on the adoptive parents.…”
Section: Summary Of Resultsmentioning
confidence: 99%
See 3 more Smart Citations